Pengaruh olahraga sepeda statis terhadap peningkatan fungsi kognitif pada dewasa muda dengan gaya hidup sedentari - Firdaus, Muhammad Ghifari; Rahmi, Upik; Salasa, Sehabudin (Physical Education Departement of University PGRI Jombang, 2025)
The sedentary lifestyle phenomenon among young adults, particularly university students, shows a notably high duration, averaging 8–12 hours per day. This condition is associated with a decline in cognitive function. One potential intervention to address this issue is stationary cycling, as this activity can increase levels of Brain-Derived Neurotrophic Factor (BDNF), which plays a crucial role in maintaining and enhancing cognitive performance. This study aimed to examine the effects of stationary cycling exercise on cognitive function among sedentary young adults. The research employed a quasi-experimental design with a pretest–posttest control group approach. A total of 40 students from the Indonesia University of Education were selected using Federer’s formula and purposive sampling technique. The participants were divided into two groups: an intervention group (n=20) and a control group (n=20). The intervention group performed moderate-intensity stationary cycling (60–80 RPM) for 30 minutes, three times a week for four weeks. Meanwhile, the control group received no intervention to observe natural changes without external influence. The results revealed an improvement in cognitive function within the intervention group, indicated by decreased average completion times on TMT A (27.45→21.15) and TMT B (46.00→36.20), as well as an increased WLMT score (23.65→27.50). In contrast, the control group showed no significant changes. Statistical analysis indicated significant differences between groups in TMT A (p=0.002), TMT B (p=0.007), and WLMT (p<0.001). Therefore, stationary cycling exercise proved effective in enhancing cognitive function and can serve as a preventive strategy to support students’ brain health.